DETERMINATION OF TERMINAL VELOCITY AND FLUID VISCOSITY USING FALLING BALL VISCOMETER WITH VIDEO TRACKER APLICATION - Naila Hilmiyana Syifa; Hartono Hartono; Sulhadi Sulhadi (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract The purpose of this study is to determine the terminal velocity and fluid viscosity using falling ball viscometer with video tracker application. The terminal velocity is obtained by videoing the ball falling into a tube 115 cm long and 5 cm in diameter which has been filled with fluid and then the video is analyzed using tracker application. The fluids used are oil SAE 20W-50 and glycerin. The balls used are namely as balls I, II, and III with diameters of 1,09cm, 1,56cm, and 1,57cm. Once the terminal velocity of the sphere is known, the fluid viscosity is obtained by using Stokes law principle. The terminal velocities of balls I, II, and III in oil SAE 20W-50 are 0.247m/s, 0.250m/s, and 0.187m/s, while the terminal velocities of balls in glycerin are 0.092m/s, 0.090m/s, and 0.065m/s. The average fluid viscosity of oil SAE 20W-50 and glycerin are 0,834Ns/m2 and 1,807Ns/m2.